1994
DOI: 10.1111/j.1530-0277.1994.tb00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Pregnancy Risk‐Drinking

Abstract: The efficacy of alcohol screening questionnaires, the TWEAK, T-ACE, NET, MAST, and CAGE, in detecting periconceptional risk-drinking, > or = 1 oz absolute alcohol/day, was investigated in 4743 African-American women attending an inner-city prenatal clinic who had reported ever drinking. Sensitivity, specificity, positive predictive value, efficiency, follow-up rates, and receiver operating characteristics of the questionnaires were examined to compare the overall effectiveness of the questionnaires and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
181
0
9

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(192 citation statements)
references
References 21 publications
2
181
0
9
Order By: Relevance
“…However, pregnant women tend to underreport their alcohol consumption, 34,35 and this effect is likely to increase during the course of pregnancy. 32,36 Previous studies have shown that women who drink the most around the time they discover they are pregnant, as assessed by AAD and AADD, are more likely to continue to drink throughout pregnancy, and to drink in binge patterns, although both the self-reported and the actual levels of consumption are usually reduced. [32][33][34][35][36] Therefore, asking the women about their drinking habits around the time of conception seems to better reflect the actual amount of alcohol consumption over the course of the pregnancy than repeated questionnaires.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, pregnant women tend to underreport their alcohol consumption, 34,35 and this effect is likely to increase during the course of pregnancy. 32,36 Previous studies have shown that women who drink the most around the time they discover they are pregnant, as assessed by AAD and AADD, are more likely to continue to drink throughout pregnancy, and to drink in binge patterns, although both the self-reported and the actual levels of consumption are usually reduced. [32][33][34][35][36] Therefore, asking the women about their drinking habits around the time of conception seems to better reflect the actual amount of alcohol consumption over the course of the pregnancy than repeated questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…33,37 The structured interview included the full-scale Michigan Alcoholism Screening Test 38 and T-ACE (Tolerance, Angry or Annoyance, Cut down or quit, eye opener) scales 39 to identify risk drinkers. 32 Socioeconomic status (SES) was measured by using a modified Hollingshead 2-factor index (occupation and education) of social position. 40 Dietary information at the time of delivery was determined by the Harvard Women's Nutrition Questionnaire, 41 which has been validated for low-income pregnant women.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifestyle dimension was represented by the variables: smoking and alcohol consumption by the woman and use of illicit drugs by the couple. We considered cases of inappropriate use women who had two or more positive responses to the instrument Tolerance-Worry-Eye-opener-Amnesia-Cut-down (TWEAK), 19 previously adapted and validated for use in Brazil. 12 For identifi cation of drug consumption, we used the Non-Student Drug Use Questionnaire (NSDUQ -Portuguese version).…”
Section: Methodsmentioning
confidence: 99%
“…The T-ACE (Tolerance, Annoyed by criticism, Cut down, Eye-opener) 14 and the TWEAK (Tolerance, Worry about drinking, Eye-opener, Amnesia, K/Cut down) [15][16][17] have been validated as reliable screening instruments for obstetrical practice, but, again, heavy drinkers are the primary targets of these two instruments, and they do not identify more moderate or light drinkers or users of illicit drugs.…”
Section: Introductionmentioning
confidence: 99%